2008
DOI: 10.1063/1.2931947
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous oxidation of disordered fcc FePt nanoparticles

Abstract: In this work we present new results on spontaneous oxidation of disordered fcc FePt nanoparticles. The "as-made" oleic acid and oleylamine coated FePt nanoparticles of average size 4 nm synthesized by a high-boiling coordinating solvent method were exposed to air over a period of days and characterized structurally and magnetically by means of different techniques such as XANES, XPS, EXAFS, and SQUID magnetometry. The "as-made" FePt nanoparticles stabilize in the disordered fcc structure and have a very low ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 29 publications
3
25
0
Order By: Relevance
“…This shows significant variation in the bond lengths, and these have been also given in Table . As we mentioned above for the 55-atom nanoparticles, these bond lengths are comparable with the experimental values on larger nanoparticles.…”
Section: Results and Discussionsupporting
confidence: 88%
“…This shows significant variation in the bond lengths, and these have been also given in Table . As we mentioned above for the 55-atom nanoparticles, these bond lengths are comparable with the experimental values on larger nanoparticles.…”
Section: Results and Discussionsupporting
confidence: 88%
“…Catalyst morphologies were varied between discrete, 5−6 nm diameter nanoparticles to near monolayer coverages by controlling the XPSdetermined Fe loadings between 2.0 × 10 −10 and 2.9 × 10 −9 mol Fe /cm 2 (Table S1). 20 The Fe 2 O 3 composition was confirmed with both XPS 30 and X-ray absorption spectroscopy (Figures S2 and S3), 31,32 and STM imaging showed that all structures formed with a consistent apparent height of ∼0.5 nm (Figure S4) that corresponds to a bilayer stacking of the O−Fe−Fe−O unit in the 2L-Fe 2 O 3 /Au catalysts. 20 The 2L-Fe 2 O 3 /Au catalysts were transferred out of the UHV chamber for electrochemical testing under ambient conditions in 0.1 M KOH electrolyte.…”
Section: ■ Results and Discussionmentioning
confidence: 75%
“…For naked 3d elemental nanomagnets (Fe, Co, Ni) as well as for alloys (e.g. FePt or CoPt) one can expect a strong deterioration of the targeted magnetic properties under ambient conditions [ 67 68 ]. For FePt alloy NPs, we recently investigated the oxidation behavior in more detail by XPS and signal modeling taking into account the spherical shape of NPs [ 66 ].…”
Section: Resultsmentioning
confidence: 99%